Material Properties of Laser-Welded Thin Silicon Foils. (28th July 2013) - Hessmann, M. T.; Kunz, T.; Voigt, M.; Cvecek, K.; Schmidt, M.; Bochmann, A.; Christiansen, S.; Auer, R.; Brabec, C. J.
Abstract : An extended monocrystalline silicon base foil offers a great opportunity to combine low-cost production with high efficiency silicon solar cells on a large scale. By overcoming the area restriction of ingot-based monocrystalline silicon wafer production, costs could be decreased to thin film solar cell range. The extended monocrystalline silicon base foil consists of several individual thin silicon wafers which are welded together. A comparison of three different approaches to weld 50 μ m thin silicon foils is investigated here: (1) laser spot welding with low constant feed speed, (2) laser line welding, and (3) keyhole welding. Cross-sections are prepared and analyzed by electron backscatter diffraction (EBSD) to reveal changes in the crystal structure at the welding side after laser irradiation. The treatment leads to the appearance of new grains and boundaries. The induced internal stress, using the three different laser welding processes, was investigated by micro-Raman analysis. We conclude that the keyhole welding process is the most favorable to produce thin silicon foils.